RHETORICAL SKILLS UTILIZED BY FOOTBALL COMMENTATORS: QUANG HUY FROM V.LEAGUE AND IAN DARKE FROM CHAMPIONS LEAGUE = Các biện pháp tu từ được sử dụng bởi 2 bình luận viên bóng đá: quang huy từ V.League và Ian Darke từ Champions League - Phạm, Thị Thanh Quý (2020)
Football commenting requires professional language skills. These skills help viewers keep insightful tracking with every move of the game. Rhetorical skills are parts of the language game in the match. Therefore, this research aims at exploring types of rhetorical skills utilized in the match, their frequency and purposes. Two matches from Vietnamese and British television are selected for the investigation of this research. Qualitative research is the main method using the instruments of observation, critical analysis and interpretation. The study shows that Metaphor and Metonymy were employed with the highest frequency in order to make the two commentators’ speech become more fluent and effective. Additionally, a small number of other devices are occasionally used, for instance: Euphemism, Exaggeration, Rhetorical Questions, Personification and Simile. With the findings collected, several implications are made for the readers to understand thoroughly the strategies of using language skills in football commentary and for the students to gain further source of references for their linguistic study.